Juridical Review of Illegal Fishing Perpetrators: Analysis of Law Number 45 Year 2009 - Yuspan Zalukhu (LEGAL BRIEF, 2022)
Illegal fishing comes from the word illegal which means illegal or unofficial. The term illegal fishing is popularly used by law enforcement officers and related agencies for criminal acts in the fisheries sector. From this it can be seen that the term illegal fishing is also used in official events by state institutions. The breadth of Indonesia's seas and the many fisheries potentials owned by Indonesia make foreign ships steal marine wealth, especially fisheries in Indonesian territory, which is also called illegal fishing activities. Many types of illegal fishing carried out by foreign vessels in Indonesian waters do not have SIUP, do not have SIPI, do not have SIKPI, falsify permits, and use hazardous materials to catch fish. The purpose of this research is (1) to find out the types of illegal fishing activities carried out by foreign ships in Indonesian waters (2) to find out the obstacles and efforts made by the government in enforcing illegal fishing actions. The research method used in this research is descriptive analytical with a normative juridical approach. Data collection techniques are carried out through literature review to obtain secondary data and qualitative data analysis or analyze problems from the point of view according to the provisions of applicable laws or regulations. The results of the research stated that the government's efforts to enforce the law on illegal fishing with the issuance of Presidential Decree no. 115 of 2015 is the latest breakthrough by the Jokowi-Jusuf government. In this Presidential Decree, it is clear that the problem of illegal fishing is an acute problem. The sinking of fishing boats for illegal fishing has only received great attention in recent years, which is evidence that law enforcers are implementing tougher and stricter laws as well as being a means of threat to prevent potential fish thieves from committing crimes in the fisheries sector.